The Effect of Reiki on Sexual Function and Sexual Self-Confidence in Women with Sexual Distress - Barut, Suemeyye; Baransel, Esra Sabanci; Ucar, Tuba (Springer, 2024)
AimStudies have reported that Reiki reduces several symptoms regarding hypertension, cancer, sleep disorders, psychological problems, and menstrual cycle. Reiki may also have positive effects on sexuality. Therefore, this study aimed to determine the effect of Reiki on sexual function and sexual self-confidence in women with sexual distress. This randomized controlled study was conducted with women between the ages of 15-49 years who were registered at a family health center in the eastern region of Turkey and had sexual distress. Women experienced more sexual difficulties than men. Therefore, the sample of this study was women. The sample of the study consisted of 106 women, 53 in the experimental group and 53 in the control group. Women in the experimental group received Reiki once a week for four weeks, while no intervention was applied to those in the control group. Data were collected using the Female Sexual Distress Scale-Revised (FSDS-R), the Arizona Sexual Experiences Scale (ASEX), and the Sexual Self-confidence Scale (SSS). The levels of sexual distress, sexual function, and sexual self-confidence of women in both groups were similar before the intervention, and the difference between the groups was not statistically significant (p > 0.05). After the Reiki application, the FSDS-R and ASEX mean scores of women in the experimental group significantly decreased, while their SSS mean score significantly increased, and the difference between the groups was statistically significant (p < 0.05). In the present study, Reiki was associated with reduced sexual distress, positive outcomes in sexual functions, and increase sexual self-confidence in women with sexual distress. Healthcare professionals may find Reiki to positively enhance women's sexuality.
Keywords: Reiki; Sexual distress; Sexual self-confidence; Sexual experience; Turkiye